2021
DOI: 10.1007/s40200-020-00696-w
|View full text |Cite
|
Sign up to set email alerts
|

Effects of propolis supplementation on glycemic status, lipid profiles, inflammation and oxidative stress, liver enzymes, and body weight: a systematic review and meta-analysis of randomized controlled clinical trials

Abstract: The aim of meta-analysis was to assess the effects of propolis on markers of oxidative stress, lipid profiles, inflammation and glycemic control, liver enzymes, and weight control. The heterogeneity between the included studies was indicated using the Cochrane's Q test and I-square (I 2 ) statistic. 14 trials were included in this meta-analysis. Our meta-analysis indicated a significant reduction in fating glucose

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 47 publications
2
20
1
Order By: Relevance
“…A recent meta-analysis in humans indicated that propolis supplementation resulted in a significant reduction in FBS and insulin, which was followed by a significant decrease in IR assessed by HOMA-IR in patients with chronic diseases. 45 In the present study, we failed to find any effect on the serum levels of TC, TG and HDL-C in the propolis group vs. the placebo group. Our results are similar to findings by Fukuda et al 46 by supplementing 226.8 mg d −1 of propolis extract for 8 weeks in T2DM patients and those by Soleimani et al 28 by administrating 500 mg d −1 propolis for 4 months in patients with NAFLD.…”
Section: Papercontrasting
confidence: 69%
See 1 more Smart Citation
“…A recent meta-analysis in humans indicated that propolis supplementation resulted in a significant reduction in FBS and insulin, which was followed by a significant decrease in IR assessed by HOMA-IR in patients with chronic diseases. 45 In the present study, we failed to find any effect on the serum levels of TC, TG and HDL-C in the propolis group vs. the placebo group. Our results are similar to findings by Fukuda et al 46 by supplementing 226.8 mg d −1 of propolis extract for 8 weeks in T2DM patients and those by Soleimani et al 28 by administrating 500 mg d −1 propolis for 4 months in patients with NAFLD.…”
Section: Papercontrasting
confidence: 69%
“…A recent meta-analysis in humans indicated that propolis supplementation resulted in a significant reduction in FBS and insulin, which was followed by a significant decrease in IR assessed by HOMA-IR in patients with chronic diseases. 45…”
Section: Discussionmentioning
confidence: 99%
“…It seems that the controversies in outcomes of researches might be related to differences in form and amount of used propolis, the study population, duration of intervention or the effects of confounders such as change in www.nature.com/scientificreports/ dietary intakes. Although, finding of current meta-analysis showed that propolis had no significant effects on anthropometric indices 33 . In preclinical studies, several anti-obesity mechanisms for propolis are considered.…”
Section: Discussionmentioning
confidence: 62%
“…In another study, a 900 mg per day supplementation with the Brazilian green propolis capsules for 18 weeks improved the antioxidant function by increasing the levels of glutathione and total polyphenols as well as decreasing serum carbonyls and lactate dehydrogenase activity in T2D patients compared to placebo ( Zhao et al, 2016 ). Moreover, recent systematic reviews and meta-analyses of these clinical trials have cumulatively reported the antidiabetic properties of various forms of propolis supplements in T2D patients ( Gheflati et al, 2021 ; Hallajzadeh et al, 2021 ). Similarly, some natural products found in the Egyptian propolis have the potential to inhibit the signaling pathways involved in SARCoV-2 binding and entry into the host cells in silico and in vivo ( Berretta et al, 2020 ).…”
Section: Herbal Medications and Natural Products In The Management Of...mentioning
confidence: 99%